THE ENGLISH TEACHERS’ PERCEPTION TOWARD THE DYNAMICS OF THE SCHOOL BASED CURRICULUM AND THE 2013 CURRICULUM AT SMAN 1, SMAN 2, SMAN 3, AND SMKN 1 TOLITOLI - Arniyati Arniyati (Jurnal Madako Education, 2020)
The  purpose  of  this  research  is  to  discribe  the  English  teachers’ perception about the Dynamics of the implementation of the school based curriculum and the 2013  curriculum.  This research  conduct  in  four  defferent  schools,  they  were  SMAN  1, SMAN 2, SMAN 3, and SMKN 1 Tolitoli where the repondents were two English teacher from each school. In collecting the data, the researcher give questionnaire to all of the respondents. To get more deep information the researcher also apply interview to five respondents. The result of the interv iew show that the good curriculum to be implemented in the school is the school based curriculum with the spporting factors such as the method used in teaching, the process of evaluation and the the teachers’ time in teaching. Then the result of the questionnaire show that the percentage is 55%, while the percentage of the 2013 curriculum is 45%. Considering the finding of this research, the government must to carefully in taking decision in the future. Key words: The teachers’ Perception, the School Based Curriculum, the 2013 Curriculum.